Hubungan Tingkat Pengetahuan Remaja tentang Pernikahan pada Usia Remaja dengan Kejadian Pernikahan Remaja saat Pandemi Covid-19 di Kecamatan Kedungbanteng - Diah Atmarina Yuliani; Alma Merilla Alodia (LPPM Akademi Kebidanan Harapan Ibu Pekalongan, 2023)
According to WHO data from 2016, marriage by a partner or one of the partners still belongs under the definition of a child or teenager under the age of 19 years. According to research done by the Ministry of National Development Planning/Bapenas during this pandemic, some 400,500 females between the ages of 1,017 and 1,017 were at risk of getting married early because of the Covid-19 pandemic. More than 64,000 requests for marriage tax exemptions for children in 2020. This study aims to determine the correlation between teenagers' knowledge of early marriage and the occurrence of early marriage during the COVID 19 pandemic. An observational analytic analysis with a cross-sectional approach was the methodology used in this study. In this study, a total of 3855 male and female teenagers in the Kedungbanteng Sub District, aged 16 to 19, were used as the population. Purposive sampling is used to choose the 97 adolescents as the sample. The findings of this study based on the Gamma test, revealed a -value of 0.020 (0.05), indicating a significant correlation between teenagers' understanding of marriage during teenage and the frequency of early marriage in Kedungbanteng Sub District, Banyumas Regency. It is hoped that young people will avoid getting married and is also expected to provide advice or guidance to teenagers about getting married at teenage in this village.